Basil (Ocimum basilicum) extracts as attractants for Bactrocera dorsalis, a pest of carambola (Averrhoa carambola) - Jisia Jimbau. (2014)
The major pest of carambola is fruit flies (Bactrocera dorsalis). An experiment has been conducted to investigate the possibility of using basil plants extract, Ocimum basilicum to attract B. dorsalis. The research is conducted in Carambola Orchard, UPM and in Entomology Laboratory, Department of Plant Protection, Faculty of Agriculture, UPM. Basil leaves essential oil was extracted using hydrodistillation method. The chemical compounds of essential oil were analyzed using Gas Chromatography-mass spectrometry (GC-MS). It is determined that basil extract have 0.14% of methy eugenol. In field experiment, the traps consist of three treatments and five replications. The treatments were the 0. basilicum extract, commercial methyl eugenol and control (without any lures). 0.2 ml of basil extract and methyl eugenol were dropped on cotton wool. The traps were set by using Completely Randomized Design (CRD). There is high significant difference (p<0.05) between basil extract and commercial methyl eugenol in trapping fruit flies, while there is no significant difference between basil extract and control treatment.. Commercial methyl eugenol is proved to be more effective to attract the fruit flies due to their higher contents of methyl eugenol, 95%. The duration of attractiveness was also longer than basil extract, which is more than 2 weeks, while basil extract can only last for one week.